Diferencias de género y comunicación: aspectos no verbales y propuestas didácticas - Encabo Fernández, Eduardo; López Valero, Amando (Didáctica. Lengua y Literatura, 2004)
The search for alternatives to the inequality of opportunities between both genders drives us to study the possible causes of this difference. In this study, specifically in the area of the Teaching of the Language and Literature, we can find that communicative aspects are at the root of the problem. From our point of view, we think communication between women and men becomes the main topic in this inequality. In communication, the verbal aspects are the most studied but in this case we want to analyse the importance of the non verbal aspects in the communication process, specifically, applying them to the gender gap. Therefore, we will search for teaching suggestions that allow us to think about a possible social and academic change related to the gender gap.
Keywords: Gender gap Sexism Communication Non verbal aspects Education